Presentation 4_Depression and anxiety among women with polycystic ovarian syndrome in low- and middle-income countries: a systematic review and meta-analysis.pdf - Atimi Atinga (22679123) (2025)
Background Increasing evidence links Polycystic ovary syndrome (PCOS) with adverse mental health outcomes, particularly depression and anxiety. These challenges may be amplified in low- and middle-income countries (LMICs) due to limited awareness, restricted healthcare access, and sociocultural stigma. Objectives To estimate the pooled prevalence of depression and anxiety among women of reproductive age with PCOS in LMICs and to examine clinical factors associated with these outcomes. Methods Following PRISMA guidelines (PROSPERO CRD420251069068), we systematically searched PubMed, Scopus, Web of Science, and CINAHL for studies published between January 2005 and June 2025. Eligible studies included observational research reporting the prevalence of depression and/or anxiety in women aged 15–49 years with clinically diagnosed PCOS and assessed using validated tools. Data were pooled using a random-effects model. Subgroup and meta-regression analyses explored variations by study design, age, body mass index (BMI), country, and assessment tools. Heterogeneity was quantified with the I² statistic, and publication bias was assessed using funnel plots and Egger's test. Study quality was evaluated with the Joanna Briggs Institute checklist. Results From 3,860 records, 40 studies met the inclusion criteria. All were rated low risk of bias (quality scores 75%–100%). The pooled prevalence of depression was 51% (95% CI: 43–59; I² = 97%), and anxiety was 45% (95% CI: 36–54; I² = 96%). The highest prevalence was observed among women aged 20–25 years (depression: 63%; anxiety: 56%) and in studies conducted in India (depression: 55%; anxiety: 51%). Clinical features such as infertility, hirsutism, and acne showed non-significant associations with depression or anxiety. No publication bias was detected. Conclusion Depression and anxiety are highly prevalent among women with PCOS in LMICs, affecting nearly half of this population. These findings underscore the urgent need for integrating routine mental health screening and culturally tailored interventions into PCOS management in resource-limited settings. Systematic Review Registration PROSPERO CRD420251069068.